2014
DOI: 10.7554/elife.01833
|View full text |Cite
|
Sign up to set email alerts
|

Auditory synapses to song premotor neurons are gated off during vocalization in zebra finches

Abstract: Songbirds use auditory feedback to learn and maintain their songs, but how feedback interacts with vocal motor circuitry remains unclear. A potential site for this interaction is the song premotor nucleus HVC, which receives auditory input and contains neurons (HVCX cells) that innervate an anterior forebrain pathway (AFP) important to feedback-dependent vocal plasticity. Although the singing-related output of HVCX cells is unaltered by distorted auditory feedback (DAF), deafening gradually weakens synapses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 50 publications
6
73
1
Order By: Relevance
“…Despite evidence indicating that feedback shapes HVC auditory selectivity, a significant challenge to this STDP model is that the singing-related action potential activity of HVC X cells is entirely insensitive to feedback perturbations [37,38]. Moreover, studies from our group using intracellular recordings in singing birds also reveal that the singingrelated synaptic activity of HVC X cells is unaltered by acute manipulations of auditory feedback [57]. Thus, how and when auditory feedback-related information impinges on HVC remains unclear.…”
Section: Developmental Origins Of Auditory -Vocal Mirroringmentioning
confidence: 84%
See 3 more Smart Citations
“…Despite evidence indicating that feedback shapes HVC auditory selectivity, a significant challenge to this STDP model is that the singing-related action potential activity of HVC X cells is entirely insensitive to feedback perturbations [37,38]. Moreover, studies from our group using intracellular recordings in singing birds also reveal that the singingrelated synaptic activity of HVC X cells is unaltered by acute manipulations of auditory feedback [57]. Thus, how and when auditory feedback-related information impinges on HVC remains unclear.…”
Section: Developmental Origins Of Auditory -Vocal Mirroringmentioning
confidence: 84%
“…Interestingly, while most HVC X neurons in anaesthetized songbirds display strong and selective auditory responses, less than half of HVC X cells that display singing-related activity also respond to song playback during periods of quiet wakefulness [35,38,73,74]. Furthermore, studies in adult zebra finches reveal that auditory activity can only be detected in HVC X and most other HVC cells when the animal is sedated, anaesthetized or asleep [57,62,63,77]. Indeed, auditory responses in the HVC of sedated zebra finches are strongly suppressed by arousing stimuli, such as a brief air puff delivered to the bird's chest [62].…”
Section: Role In Perception and The Effects Of Auditory Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…The recordings could survive severe mechanical disturbances and remain stable for 20 min while rats explored their environment freely. Other groups have shown that sharp intracellular recordings could be obtained and maintained in freely moving birds (Long et al 2010;Hamaguchi et al 2014;Kosche et al 2015;Vallentin and Long 2015) and mice (English et al 2014;Schneider et al 2014) using a head-mountable linear microdrive. The first such recordings were made from bird premotor HVC neurons to measure the subthreshold membrane potential dynamics during singing, and the resulting recordings supported a synaptic chain-like mechanism for birdsong generation (Long et al 2010).…”
Section: Intracellular Recordings In Freely Moving Animalsmentioning
confidence: 99%